Evaluating the Long-Term Impacts of an Applied Interdisciplinary Product Development Curriculum on Food Science, Nutrition, and Packaging Science Undergraduate Students. Issue 4 (3rd July 2020) - Condrasky, Margaret; Halteman, Breanne; Sharp, Julia; Darby, Duncan
ABSTRACT: The research objective was to evaluate the long-term impacts of an Applied Interdisciplinary Product Development (AIPD) curriculum on students' self-confidence in product development skills and knowledge in various disciplines other than their own. The results of the Subject Knowledge Assessment (SKA) showed that students who completed the AIPD course did not have significantly different scores from the comparison group ( P 0.05). However, significant differences were found between the treatment and comparison groups for five of the nine statements pertaining to confidence in product development skills on the Exit Questionnaire (EQ; P < 0.05). Results from the focus groups conducted with students who participated in the AIPD course supported the results of the EQ and SKA. Therefore the conclusion can be made that students who completed the AIPD course have maintained their advanced skill level over their peers in such areas as product development skills and soft skills.